PENGARUH PERSEDIAAN DAN PIUTANG TERHADAP PROFITABILITAS PADA INDUSTRI DIBIDANG FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE2010 – 2014 - Sari, Nur Esa Purnama; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The pharmaceutical company is one of the businesses in the economy sector which has a vital role in the national economy, it really makes the Pharmaceutical industry sector had a very fierce competition in the business world. But on the other hand the pharmaceutical are assessed very favorable for investors. For investors who are looking for a profit need to pay attention to financial report that become information for investors, things to get profit namely profitability.This research is a descriptive quantitative research in order to know how the influence of inventory and accounts receivable turnover simultaneously and partially towards the profitability on eight pharmaceutical companies. The results of the research shows that partially just inventory turnover has influence towards profitability, while accounts receivable Turnover has not influence towards profitability. On the other hand, shows that simultaneously inventory turnover and accounts receivable turnover have influence towards profitability.Keyword: Inventory Turnover, Accounts Receivable Turnover, Profitability.